2015
DOI: 10.1016/j.jcot.2015.04.009
|View full text |Cite
|
Sign up to set email alerts
|

PCL-retaining versus PCL-substituting TKR – Outcome assessment based on the “forgotten joint score”

Abstract: Methods: In this retrospective study, the recently introduced ''forgotten joint score'' (FJS) was used to assess whether any differences exist between the two types of total knee replacement (TKR). FJ scores of 169 patients with PCL-retaining TKA and 178 patients with PCL sacrificing were obtained. The mean follow-up period was 3.5 years and the minimum follow-up period was 2.5 years.Results: Both groups showed high FJ scores indicating that majority of the patients were oblivious to the presence of the artifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…These values seem higher and exceeds reported FJS scores in healthy adults with no knee issues [9]. When mobile and fixed bearing TKSs were compared with follow up of three years, scores were found to be 77.2 and 61.9, which are comparable to our findings [34].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These values seem higher and exceeds reported FJS scores in healthy adults with no knee issues [9]. When mobile and fixed bearing TKSs were compared with follow up of three years, scores were found to be 77.2 and 61.9, which are comparable to our findings [34].…”
Section: Discussionsupporting
confidence: 88%
“…Mean age was 65.01 (28-91) years. All patients in the study had minimum follow up of 24 months with average follow up of 30.85 (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) months. Of the total knees 55.12% were left sided and 44.88% were right, in our group 10.63% of patients had valgus knees who underwent TKA.…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al also reported no influence of PCO and PCOR on flexion angle PCL sacrificing TKA with study involving two groups one with 1.2-mm reduction in the PCO and the other with any reduction. Similar results were found in studies done by Rajshekar K [23] Hanratty et al [24] and Bauer et al [25] on PCL sacrificing TKA whereas Arabori et al [26] on PCL substituting TKA. The significance of PCO appears to be less in the posterior stabilized or posterior-sacrificing knee prosthesis as per the previous studies.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies have compared patients’ outcomes with PCL-preserved or sacrificed TKA; generally, no significant differences were described between the two groups of patients [ 34 , 43 , 44 , 45 ]. Thippanne et al [ 43 ] reported no statistically significant differences for FJS between 169 PCL-retained TKAs and 178 PCL-sacrificed TKAs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have compared patients’ outcomes with PCL-preserved or sacrificed TKA; generally, no significant differences were described between the two groups of patients [ 34 , 43 , 44 , 45 ]. Thippanne et al [ 43 ] reported no statistically significant differences for FJS between 169 PCL-retained TKAs and 178 PCL-sacrificed TKAs. Similarly, Bieganowski et al [ 44 ] compared mean postoperative FJS in 671 TKAs; 236 were treated with a PCL preservation implant and 435 were treated with a posterior stabilized prosthesis.…”
Section: Discussionmentioning
confidence: 99%